Semi-metal compensation ferromagnetic material as well as preparation method and application thereof
By synthesizing CrFeS2 single crystal material with hexagonal NiAs type crystal structure, the problem of lack of exchange bias effect in existing semi-metallic compensation ferroferromagnets is solved, and the wide application prospect in the field of spintronics is achieved, with great verticality Magnetic anisotropy and zero-field cold exchange bias effect.
Patent Information
- Application Number
- CN202311046861.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-19
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-08-19
AI Technical Summary
There is a lack of research on the exchange bias effect of existing semi-metallic ferroferrous magnets, and no exchange bias effect was found in experimentally synthesized materials, limiting their application in the field of spintronics.
CrFeS2 single crystal material with hexagonal NiAs type crystal structure was developed and synthesized, which exhibited significant characteristics in terms of extreme perpendicular magnetic anisotropy and zero-field cold exchange bias effects.
It has achieved wide application prospects in the field of spintronics, with great perpendicular magnetic anisotropy and zero-field cold exchange bias effect, 5K coercive field is 6T, and 5K zero-field cold exchange bias field can reach 0.8T. And the direction of exchange bias can be controlled by unidirectional magnetic fields of different sizes.
Smart Images

Figure CN119495481A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a semi-metallic compensating ferrimagnetic material with extremely large perpendicular magnetic anisotropy and zero-field cold exchange bias, and a preparation method and application thereof. Background Art
[0002] Semimetals are a class of materials with a spin polarization rate of 100% that behaves as a metal in one spin direction and as a semiconductor or insulator in the other spin direction. They are important materials in the application of spintronic devices.
[0003] Most of the half-metal materials discovered so far are ferromagnetic materials. As the requirements for device integration density continue to increase, ferromagnetic materials will be difficult to meet the requirements, and the stray fields they generate will hinder the integration density of the device. Compensated ferrimagnets and antiferromagnets with very small or even zero magnetic moments are more ideal materials. Due to the high symmetry of antiferromagnets, their upper and lower spin sublattices are equivalent and have the same state density, and the spin polarization is restricted to zero, making it impossible to achieve a half-metal antiferromagnet. Ferrimagnets have low symmetry, and even when magnetic compensation is performed, the two sets of spin sublattices are not equivalent, so half-metallic compensated ferrimagnets can be achieved.
[0004] Half-metallic compensated ferrimagnets combine the characteristics of 100% polarizability and zero stray field, and have broad application prospects, such as being ideal materials for spin-polarized scanning tunneling microscope tips and anchor layers for spin valve devices. Developing and synthesizing new half-metallic compensated ferrimagnets is an important step towards realizing their applications.
[0005] The phenomenon that the hysteresis loop moves along a certain magnetic field axis is called exchange bias. Although the origin of exchange bias is still unclear, exchange bias has been widely used in scientific and technological fields, such as high-density magnetic storage. Through field cooling, exchange bias can be achieved on ferromagnetic / antiferromagnetic or ferrimagnetic thin film heterojunctions. Overall, the exchange bias effect is related to the unidirectional anisotropy formed by the interaction between different magnetic phases. In addition to field cooling, the commonly used methods for forming unidirectional anisotropy can also include depositing an antiferromagnetic layer on a saturated ferromagnetic layer and using residual magnetization zero-field cooling.
[0006] Recently, in the compensated ferrimagnetic Mn-Pt-Ga system and the antiferromagnetic Fe x Giant exchange bias effects have been found in NbS2. In these systems, the ferromagnetic order or spin glass order introduced by positional disorder interacts with the ferrimagnetic or antiferromagnetic order to form a giant exchange bias effect.
[0007] Theoretically, through material settings, huge exchange bias can be achieved by utilizing position disorder in half-metallic compensated ferrimagnets. Currently, the only half-metallic compensated ferrimagnet synthesized experimentally is Mn2Ru. 0.5 Ga thin film, Mn 1.5 FeV0.5 Al and Mn2Co 0.5 V 0.5 Al alloys. No exchange bias effect is found in these semi-metallic compensated ferrimagnetic materials. Therefore, it is necessary to explore semi-metallic compensated ferrimagnets with exchange bias effect. Summary of the invention
[0008] Therefore, the object of the present invention is to develop and synthesize half-metallic compensated ferrimagnets with giant zero-field cold exchange bias effect.
[0009] The inventors of the present invention have found through a large number of experimental studies that CrFeS2 single crystals with a hexagonal NiAs crystal structure have a huge zero-field cold exchange bias effect while having extremely large perpendicular magnetic anisotropy, and therefore have broad application prospects in the field of spin electronics.
[0010] In a first aspect, the present invention provides a semi-metallic compensated ferrimagnetic material, the chemical formula of which is CrFeS2, which has a hexagonal NiAs type crystal structure and belongs to space group No. 194.
[0011] According to the semi-metallic compensated ferrimagnetic material provided by the present invention, the material has a large perpendicular magnetic anisotropy. In various embodiments of the present invention, the easy axis of magnetization of the material is parallel to the c-axis of the crystal structure, and the coercive field is 6 T at 5 K. The easy axis of magnetization refers to the magnetic easy axis or easy magnetization axis if the ferromagnet is most easily magnetized along a certain axis or direction.
[0012] According to the semi-metallic compensated ferrimagnetic material provided by the present invention, the material has magnetically compensated ferrimagnetic properties. In various embodiments of the present invention, the Curie temperature of the material is >350K, and the magnetic compensation temperature is 185±2K.
[0013] According to the semi-metallic compensated ferrimagnetic material provided by the present invention, the material still has an anomalous Hall effect when magnetic compensation occurs.
[0014] According to the half-metallic compensated ferrimagnetic material provided by the present invention, the material has a large exchange bias field. In various embodiments of the present invention, at 5K, the exchange bias field of the material can reach 0.8T.
[0015] The semi-metallic compensated ferrimagnetic material provided by the present invention has the characteristics of extremely large perpendicular magnetic anisotropy and magnetic compensation characteristics, so that the material can realize zero-field cold large exchange bias, and the direction of the exchange bias can be regulated by unidirectional magnetic fields of different sizes.
[0016] In a first aspect, the present invention provides a method for preparing the above-mentioned semi-metallic compensated ferrimagnetic material, the preparation method comprising:
[0017] (1) Encapsulating raw materials of Cr powder, Fe powder and sulfur block and transmission medium iodine in a vacuum quartz tube;
[0018] (2) placing the quartz tube encapsulated with the raw materials in a heating furnace, heating at 780-920° C. for 4-30 days, synthesizing CrFeS2 single crystals by chemical vapor transport method, and then quenching to a room temperature to obtain the semi-metallic compensated ferrimagnetic material.
[0019] According to the preparation method provided by the present invention, the molar ratio of Cr powder, Fe powder and sulfur block in step (1) can be 20-25:20-25:50-60, and most preferably 23:23:54. Preferably, the purity of the raw materials in step (1) is >99.9%.
[0020] According to the preparation method provided by the present invention, the step (1) further comprises the operation of cleaning the quartz tube with an inert gas after the raw materials are loaded.
[0021] In a preferred embodiment of the present invention, the vacuum pressure in the vacuum quartz tube after packaging in step (1) is less than 2×10 -3 Pa.
[0022] According to the preparation method provided by the present invention, the heating furnace in step (2) can be a muffle furnace, a pit furnace and / or a temperature zone furnace.
[0023] In some embodiments of the present invention, the heating process described in step (2) may include: placing the quartz tube encapsulating the raw materials into a pit furnace, heating from room temperature to 780-820°C over 2-6 days, heating to 880-920°C over 2-6 days, and then keeping warm at 880-920°C for 2-6 days.
[0024] In other embodiments of the present invention, the heating process described in step (2) may include: placing the quartz tube encapsulated with the raw materials in a muffle furnace and heating it from room temperature to 780-900°C for pre-firing over 2-6 days, and then placing it in a temperature zone furnace, heating the high temperature end of the temperature zone furnace to 905-915°C over 2-4 hours, and heating the low temperature end to 885-895°C over 2-4 hours, and then maintaining it at this temperature for 10-30 days.
[0025] In some other embodiments of the present invention, the heating process described in step (2) may include: placing the quartz tube encapsulating the raw materials into a temperature zone furnace, heating the high temperature end of the temperature zone furnace to 905-915°C over 2-6 days, heating the low temperature end to 885-895°C over 2-6 days, and then maintaining the temperature for 10-30 days.
[0026] In a third aspect, the present invention provides the use of the semi-metallic compensated ferrimagnetic material of the present invention or the semi-metallic compensated ferrimagnetic material prepared according to the method of the present invention as a hard magnetic material.
[0027] In a fourth aspect, the present invention provides the use of the half-metal compensated ferrimagnetic material of the present invention or the half-metal compensated ferrimagnetic material prepared according to the method of the present invention in a spintronic device.
[0028] Compared with existing materials, the CrFeS2 material provided by the present invention has the following beneficial effects:
[0029] 1. The material of the present invention has extremely large perpendicular magnetic anisotropy and zero-field cold exchange bias, the 5K coercive field is 6T, and the 5K zero-field cold exchange bias field can reach 0.8T.
[0030] 2. The material of the present invention can control the direction of exchange bias by means of unidirectional magnetic field cooling of different magnitudes.
[0031] 3. The material of the present invention has magnetic compensation properties, and even with compensation, it still exhibits an anomalous Hall effect.
[0032] 4. The raw materials used in the present invention do not contain rare earth elements, which reduces the dependence of hard magnetic materials on rare earths and reduces the preparation cost of materials.
[0033] The CrFeS2 semi-metallic compensated ferrimagnetic material provided by the present invention can be applied to the rare earth-free hard magnetic field or the spin electronics field. When used in the hard magnetic field, the dependence of hard magnetic materials on rare earths can be reduced, and the preparation cost of the materials can be reduced. When used in the spin electronics field, a new type of compensated ferrimagnetic tunnel junction can be developed. The semi-metallic characteristics, strong perpendicular magnetic anisotropy and zero-field cold exchange bias of the material correspond to the characteristics of the huge tunneling magnetoresistance of the tunnel junction, insensitivity to external magnetic field interference, and simple structure without the need for additional exchange bias structure. The strong perpendicular magnetic anisotropy of the material, the internal magnetic anisotropy field below room temperature is higher than 30T, and it is expected to correspond to a resonance frequency exceeding 1THz, and an ultrafast spin switch of the picosecond level can be developed. The semi-metallic characteristics of the material eliminate the channels of some spin scattering, which is expected to reduce the magnetic damping coefficient of the material. Combined with the smaller net magnetic moment of the material, it is expected to use a smaller spin current to excite oscillation, so it can be used for spin transfer torque nano oscillators and spin orbit torque nano oscillators in the terahertz frequency band. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0035] Figure 1 The photograph (a), structural schematic diagram (b) and X-ray diffraction pattern (c) of the CrFeS2 sample prepared in Example 1 of the present invention.
[0036] Figure 2 This is the thermomagnetic curve of the CrFeS2 sample prepared in Example 1 of the present invention.
[0037] Figure 3 The magnetization curves at different temperatures and the variation of saturation magnetic moment with temperature of the CrFeS2 sample prepared in Example 1 of the present invention.
[0038] Figure 4 The Hall resistivity curves of the CrFeS2 sample prepared in Example 1 of the present invention at different temperatures vary with magnetic field.
[0039] Figure 5 The results of the influencing factors of the exchange bias effect of the CrFeS2 sample prepared in Example 1 of the present invention, wherein (a) shows the result of the exchange bias effect and the initial magnetic field direction; (b) shows the training effect result of the exchange bias.
[0040] Figure 6 The low-temperature Hall curves of the CrFeS2 sample prepared in Example 1 of the present invention with different magnetic field cooling, wherein (a) is the Hall curve obtained by testing at 5K with different fields after magnetizing at room temperature with a positive field; (b) is the Hall curve obtained by testing at 5K with different fields after magnetizing at room temperature with a negative field.
[0041] Figure 7 The coercive field and exchange bias field of the CrFeS2 sample prepared in Example 1 of the present invention at 5K vary with the field cold field, wherein: Figure 7 Figure (a) shows the curve of coercive field changing with field cold field at 5K, the horizontal axis is field cold field, and the vertical axis is coercive field; Figure 7 Figure (b) shows the change curve of exchange bias field with field cooling field at 5K. The horizontal axis is the field cooling field and the vertical axis is the exchange bias field. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, rather than for limiting the scope of the present invention.
[0043] The raw materials and equipment used in the embodiments of the present invention include:
[0044] High purity elemental Cr powder, Fe powder, S block and elemental iodine.
[0045] The muffle furnace was produced by Tianjin Kaiheng Electrothermal Technology Co., Ltd., model KLJ-13Y; the magnetic measurement system (MPMS (SQUID-VSM)) and the comprehensive physical property measurement system (PPMS-16T and PPMS-9T) were produced by Quantum Design (USA).
[0046] Example 1
[0047] 1. Use 1g of Cr powder, Fe powder and sulfur block with a molar ratio of 23:23:54 and 0.1g of transmission medium iodine to encapsulate in a quartz tube with an outer diameter of 20mm, an inner diameter of 18mm and a length of 120mm. After cleaning with Ar gas, evacuate to a high vacuum (vacuum degree less than 2×10 -3 Pa) and sealed.
[0048] 2. Place the quartz tube containing the raw materials in a pit furnace for heating. The heating process is: heating from room temperature to 800°C over 96 hours, then heating to 900°C over another 96 hours, and maintaining at 900°C for 96 hours.
[0049] 3. Put the heated quartz tube into water and quench it to room temperature to obtain the semi-metallic compensated ferrimagnetic material CrFeS2 sample of the present invention.
[0050] Performance Testing
[0051] 1. Structural Characterization
[0052] The CrFeS2 single crystal sample grown by chemical vapor transport in Example 1 was observed using an optical microscope. Figure 1 As shown in Figure (a), the side length of the square is 1 mm. The sample is a NiAs-like structure with a space group of P63 / mmc (No.194). Cr and Fe atoms occupy the 2a (0,0,0) position, and S atoms occupy the 2c (1 / 3,2 / 3,1 / 4) position. The side view and top view of the structure are shown in Figure 1 As shown in Figure (b), its single crystal X-ray diffraction spectrum is as follows Figure 1 As shown in Figure (c).
[0053] 2. Magnetic Measurement
[0054] The CrFeS2 sample prepared in Example 1 of the present invention was measured using a superconducting quantum interference vibration magnetometer. At low temperature of 5K, a 7T magnetic field was added to magnetize the sample and then the field was reduced to zero. The zero-field heating thermomagnetic curve (MT curve) is as follows: Figure 2 shown.
[0055] The magnetic moment of the MT curve changes from positive to negative when crossing the zero point, which confirms that the material is a compensated ferrimagnet. The magnetic compensation temperature T comp It is about 185±2 K. The 350K magnetic moment has a certain value that is not zero, which confirms that the Curie temperature of the material is greater than 350K.
[0056] The magnetization curves (MH curves) of the CrFeS2 sample of the present invention at different temperatures were measured using a vertical 9T magnetic field. Figure 3The saturation magnetic moment can be extracted from the MH curve as shown in Figure (a). Figure 3 As shown in Figure (b). Among them, Figure 3 (a) is the magnetization curve at different temperatures, where the horizontal axis is the magnetic field and the vertical axis is the magnetization intensity; Figure 3 (b) is a scatter plot of saturation magnetization intensity versus temperature, where the horizontal axis is temperature and the vertical axis is saturation magnetization intensity.
[0057] As the temperature increases, the saturation magnetic moment increases slightly and then decreases, dropping to zero at the magnetic compensation temperature. Then, as the temperature increases to 300K, the saturation magnetic moment increases.
[0058] 3. Transport Measurement
[0059] The Hall curves of the CrFeS2 samples prepared in the embodiment of the present invention at different temperatures were measured using a comprehensive physical property measurement system. Figure 4 As shown, the horizontal axis is the magnetic field and the vertical axis is the Hall resistivity. Figure 4 The Hall signals at 80K and 240K are opposite in sign, which further confirms the magnetic compensation property of the material. The coercive field of the sample is 6T at 5K and 2T at 300K.
[0060] The influencing factors of the exchange bias effect of the CrFeS2 sample prepared in the embodiment of the present invention were determined by using a comprehensive physical property measurement system. The results of the exchange bias effect and the initial magnetic field direction are shown in FIG. Figure 5 As shown in Figure (a), after the sample is magnetized by applying a positive field at room temperature, the field is reduced to zero, and then the temperature is cooled to 5K with zero field. The Hall curves are tested from positive and negative fields respectively. From the results, it can be seen that the initial magnetic field direction has almost no effect on the low-temperature exchange bias effect. The training effect of exchange bias is shown in Figure 5 As shown in Figure (b), after the sample is magnetized by applying a positive field at room temperature, the field is reduced to zero, and then the temperature is cooled to 5K with zero field. The Hall curve is measured three times in succession. The results show that the exchange bias of the sample has no obvious training effect.
[0061] The Hall curve results of the sample at 5K after being magnetized and cooled with different magnetic fields are as follows: Figure 6 As shown, Figure 6 Figure (a) shows the Hall curves obtained by testing the room temperature magnetization with positive field and then cooling to 5K with different fields. Figure 6 Figure (b) shows the Hall curves obtained by testing the temperature drop to 5K after magnetization at room temperature with a negative field and then cooling with different fields. Figure 6 From the results, it can be seen that the field cooling field can significantly affect the exchange bias field.
[0062] The results of the changes of 5K coercive field and exchange bias with the field cold field are as follows: Figure 7As shown in Figures (a) and (b), the field cooling has almost no effect on the size of the coercive field, while the field cooling can significantly change the size and direction of the exchange bias field. Field cooling of different sizes in a single direction can adjust the size and direction of the exchange bias field. The exchange bias field of this sample with zero field cooling can reach 0.8T.
[0063] Although the present invention has been described to a certain extent, it is obvious that appropriate changes in various conditions can be made without departing from the spirit and scope of the present invention. It is understood that the present invention is not limited to the embodiments described, but belongs to the scope of the claims, which includes equivalent replacements of each factor described.
Claims
1. A semi-metallic compensated ferrimagnetic material, wherein the chemical formula of the semi-metallic compensated ferrimagnetic material is CrFeS2, which has a hexagonal NiAs type crystal structure and belongs to space group No.
194.
2. The semi-metallic compensated ferrimagnetic material according to claim 1, wherein: The magnetization easy axis of the material is parallel to the c-axis of the crystal structure, and the coercive field is 6T at 5K.
3. The semi-metallic compensated ferrimagnetic material according to claim 1 or 2, wherein: The Curie temperature of the material is >350K, and the magnetic compensation temperature is 185±2K.
4. The semi-metallic compensated ferrimagnetic material according to any one of claims 1 to 3, wherein: The material has an anomalous Hall effect when magnetic compensation occurs.
5. The semi-metallic compensated ferrimagnetic material according to any one of claims 1 to 4, wherein: At 5K, the exchange bias field of the material is 0.8T.
6. A method for preparing the semi-metallic compensated ferrimagnetic material according to any one of claims 1 to 5, the method comprising: (1) Encapsulating raw materials of Cr powder, Fe powder and sulfur block and transmission medium iodine in a vacuum quartz tube; (2) placing the quartz tube encapsulated with the raw materials in a heating furnace, heating at 780-920° C. for 4-30 days, synthesizing CrFeS2 single crystals by chemical vapor transport method, and then quenching to a room temperature to obtain the semi-metallic compensated ferrimagnetic material.
7. The preparation method according to claim 6, wherein: The molar ratio of Cr powder, Fe powder and sulfur block in step (1) is 20-25:20-25:50-60, preferably 23:23:
54.
8. The preparation method according to claim 6, wherein: The step (1) further comprises the operation of cleaning the quartz tube with an inert gas after the raw materials are loaded; Preferably, the vacuum pressure in the vacuum quartz tube after packaging in step (1) is less than 2×10 -3 Pa.
9. The preparation method according to claim 6, wherein: The heating furnace described in step (2) is a muffle furnace, a pit furnace or a temperature zone furnace; Preferably, the heating process described in step (2) comprises: placing the quartz tube encapsulating the raw materials in a pit furnace, heating from room temperature to 780-820° C. over 2-6 days, heating to 880-920° C. over 2-6 days, and then keeping at 880-920° C. for 2-6 days; Alternatively, the heating process in step (2) comprises: placing the quartz tube encapsulated with the raw materials in a muffle furnace and heating it from room temperature to 780-900° C. for pre-sintering over 2-6 days, then placing it in a temperature zone furnace, heating the high temperature end of the temperature zone furnace to 905-915° C. over 2-4 hours, heating the low temperature end to 885-895° C. over 2-4 hours, and then maintaining it at this temperature for 10-30 days; Alternatively, the heating process described in step (2) includes: placing the quartz tube encapsulating the raw materials into a temperature zone furnace, heating the high temperature end of the temperature zone furnace to 905-915° C. over 2-6 days, heating the low temperature end to 885-895° C. over 2-6 days, and then maintaining the temperature for 10-30 days.
10. Use of the half-metal compensated ferrimagnetic material according to any one of claims 1 to 5 or the half-metal compensated ferrimagnetic material according to any one of claims 6 to 9, said use comprising use as a hard magnetic material and use in a spintronic device.
Citation Information
Patent Citations
Half-metallic antiferromagnetic material
CN101978442A
Ferromagnetic semimetal crystal, preparation method thereof and application
CN111081868A
Ferrimagnetic material and production method thereof
JP2022026698A
Half-metallic antiferromagnetic material
WO2009116555A1